Studi Mengenai Efek Mediasi Leverage Terhadap Faktor Penentu Earning Response Coefficient Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia - Merrisya .; Rudolf L. Tobing (Jurnal Akuntansi, 2014)
ABSTRACTThis research discussed about the change of debt ratio to influence the factors which effect an Earning Response Coefficient (ERC). The sample units of this research used companies which are categorized manufacturing industrial sectors that were listing in Indonesia Stock Exchange (IDX), during the period of 2000 to 2009. Data analysis technique for the empirical research model used path analysis. The result of this research concluded that leverage had negative and significant indirect influence to ERC related to the change of beta risk, earning persistence, and reporting lags. But leverage had significant influence positively to mediate the direct effect of earning predictability to ERC.Keywords: Leverage, Earning Persistence, Earning Predictabiliy, Beta Risk, Market Reaction Earning Response Coefficient